Knowledge and Prevalence of Family Planning Measures among Community People of Chisapani, Banke - Roy, Roshan Kumar; Roy, D. K.; Bist, A.; Ghimire, S. (Journal of Nepalgunj Medical College, 2018)
Introduction: Global threat of increasing population has become a challenge to control. That’s why Family planning is a strong matter of concern for most of the developing countries like Nepal. The first family planning service in Nepal was provided by Family Planning Association Nepal (FPAN) in 1959 to provide an Integrated Package of Essential Services (IPES) that includes comprehensive counseling; family planning and sexual health services; safe abortion services; HIV and AIDS and other sexually-transmitted infection (STI) services; gynecological, prenatal, and post-natal care; and GBV care. Several studies reflect that increment in population is directly related to the level of education, low family income, and lack of awareness, strong cultural beliefs and many more. Especially, village areas of Nepal are deprived of Family Planning services and measures due to lack of coverage and other facilities. Thus knowledge regarding Family planning and contraception needs to be accessed and hence a village in Chisapani, Banke district of Nepal was chosen for this study. Objectives: The overall objectives of our study were to access the knowledge regarding Family planning, to access the practise of Contraceptive measures and to find out the contraceptive prevalence rate (CPR) among community people of Chisapani village, Banke. Material and Method: A Cross-sectional descriptive study with population size of 410 community people was performed in Chisapani, Banke; starting from 18th June to 2nd September, 2018. A pre-tested questionnaire containing structural, semi-structural and open ended questions were made as data collection tool. All the people in this study were interviewed after receiving consent as an ethical clearance. Result: 393 out of 410 (i.e. 95.85%) people in our studyhave known about Family planning via Mass Media (75.82%). Only 70.48% people responded to have used any Contraceptive measure. Depo was found to be the most used measure (i.e. 54.87%). 42.43% people have heard about emergency contraceptive pills but only 20.68% among them have ever used it. Conclusion: Though 95.85% of the respondents of our study had known about Family Planning however only 70.48% people have been using any of the contraceptive measures. Emergency contraceptive pills were used by only 20.68% of the respondents.